LEGALITAS DAN OTORITAS FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA DALAM OPERASIONAL LEMBAGA KEUANGAN SYARIAH - Muhamad Ibnu Afrelian; Imahda Khoiri Furqon (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2019)
Islamic financial institutions in their operations require legislation. In addition, practitioners of sharia economics also need a fatwa from the National Sharia Council-Indonesian Ulema Council (DSN-MUI) to guarantee the implementation of Sharia principles in sharia financial institutions. Although the fatwa is basically an advice that can be carried out or ignored, but the DSN-MUI Fatwa if it is related to positive law, the position is the same as the doctrine that is as an amplifier in the legal ruling of a qadhi in a case. The DSN-MUI fatwa also has authority and an important role in making legislation binding, and is used as a positive law in enhancing the development of sharia economics in Indonesia. The legal aspects contained in the DSN-MUI fatwa, can be seen from the absorption of the DSN-MUI fatwa in various regulations relating to the operations of Islamic financial institutions, and have been transformed into the form of laws. Thus, the legal strength of the DSN-MUI fatwa becomes binding in the operations of Islamic financial institutions